2022
DOI: 10.1016/j.apnu.2021.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and suicidal ideation in nurses with and without symptoms of secondary traumatic stress during the COVID-19 outbreak

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 49 publications
0
40
0
1
Order By: Relevance
“…Greater levels of STS among MHWs with severe FCV-19 were found in our study. This is an important finding given that STS has been linked to unfavourable mental health outcomes in MHWs and HCWs such as anxiety, depression, and suicidal ideation prior and after the onset of the coronavirus pandemic [ 16 , 53 , 54 ]. Moreover, studies during the pandemic have also found higher levels of STS in MHWs who reported being more fatigued, doubting their professional competency, as well as those who felt they had a poorer therapeutic relationship with their patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Greater levels of STS among MHWs with severe FCV-19 were found in our study. This is an important finding given that STS has been linked to unfavourable mental health outcomes in MHWs and HCWs such as anxiety, depression, and suicidal ideation prior and after the onset of the coronavirus pandemic [ 16 , 53 , 54 ]. Moreover, studies during the pandemic have also found higher levels of STS in MHWs who reported being more fatigued, doubting their professional competency, as well as those who felt they had a poorer therapeutic relationship with their patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that FCV-19 explained a significant yet relatively low percentage of STS variation. STS levels in MHWs may be related to pre-existing mental health difficulties aggravated amidst the pandemic, such as personal trauma, depression, anxiety, or sleep problems, which have previously been linked to the severity of STS and PTSD in both MHWs and HCWs [ 43 , 53 , 54 ]. Furthermore, STS may be related to workplace factors, such as lack of organizational support, workplace violence, rapid and abrupt changes in care protocols without adequate preparation and information [ 21 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has identified coronaphobia or extreme fear of coronavirus (39.4%) as the most prevalent mental health issue associated with the outbreak followed by anxiety (37%), depression (35%), and stress (26%) among frontline nurses (Al Maqbali et al, 2021; Li et al, 2021; Murat et al, 2021). These conditions, if left unmanaged, could result in even more alarming consequences such as increased suicide rates (Ariapooran et al, 2021) and may drive nurses to quit their workplace or even the nursing profession (Falatah, 2021; Irshad et al, 2020; Yáñez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Most hospital nurses experience job-related stress (Liu, Aungsuroch, et al, 2021). During the COVID epidemic, this stress was even higher, resulting in health impacts such as sleeplessness, anxiety, depression, and post-traumatic stress disorder (PTSD) in some cases (Ariapooran et al, 2021; Cao et al, 2022; Xia et al, 2021). However, we argue that support from the servant leaders lessens the impact of incivility.…”
Section: Discussionmentioning
confidence: 99%